Inhibitory effect of epirubicin-loaded lipid microbubbles with conjugated anti-ABCG2 antibody combined with therapeutic ultrasound on multiple myeloma cancer stem cells. (2nd January 2016) - Shi, Fangfang; Yang, Fang; He, Xiangfeng; Zhang, Ying; Wu, Songyan; Li, Miao; Zhang, Yunxia; Di, Wu; Dou, Jun; Gu, Ning
Abstract: Ultrasound-targeted microbubble destruction (UTMD) technique is thought to improve the chemotherapeutic agent delivery from microbubbles (MBs) in tumor tissues and reduce the side effects in non-tumor tissues. Multiple myeloma (MM) is a bone marrow cancer and remains to be an incurable disease. In this study, we used the UTMD technique to investigate the inhibitory effect of our developed novel reagent on MM cancer stem cells (CD138 − CD34 − MM CSCs) that are MM cells with CD138 − CD34 − phenotypes, responsible for MM-initiating potential, drug resistance and eventual relapse. The preparatory steps of novel reagent was first epirubicin (EPI)-loaded in the lipid MBs that was consisted of 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine- N -[methoxy(polyethylene glycol)-2000]-biotin, dipalmitoyl-phosphatidylglycerol and 25-NBD-cholesterol, then anti-ABCG2 monoclonal antibody (mAb) was conjugated onto the MB surface to form EPI-MBs+mAb. CD138 − CD34 − MM CSCs were isolated from human MM RPMI 8226 cell line by the magnetic associated cell sorting method. The results showed that the attenuated proliferation, migration and invasion ability, and increased apoptosis were observed when MM CSCs were incubated with a various agents. EPI-MBs+mAb combined with therapeutic ultrasound significantly promoted the MM CSC apoptosis compared with EPI, EPI-MBs alone or EPI-MBs+mAb without ultrasound exposure. These results suggest that the developed EPI-MBs+mAb combined with therapeutic ultrasound remarkably induced MM CSC apoptosis in vitro .